Viral Diversity and Its Relationship With Environmental Factors at the Surface and Deep Sea of Prydz Bay, Antarctica - Gong, Zheng; Liang, Yantao; Wang, Min; Jiang, Yong; Yang, Qingwei; Xia, Jun; Zhou, Xinhao; You, Siyuan; Gao, Chen; Wang, Jian; He, Jianfeng; Shao, Hongbing; et al. (Frontiers in Microbiology, 2018)
A viral metagenomic analysis of five surface and two bottom water (878 meters below surface, mbs and 3,357 mbs) samples from Prydz Bay, was conducted during February–March 2015. The results demonstrated that most of the DNA viruses were dsDNA viruses (79.73 - 94.06%, except at PBI1, 37.51%). Of these, Caudovirales (Siphoviridae, Myoviridae, and Podoviridae) phages were most abundant in surface seawater (67.67 - 71.99%), while nucleocytoplasmic large DNA viruses (NCLDVs) (Phycodnaviridae, Mimiviridae, and Pandoraviridae accounted for > 30% of dsDNA viruses) were most abundant in the bottom water (3,357 mbs). Of the ssDNA viruses, Microviridae was the dominant family in PBI2, PBI3, PBOs, and PBI4b (57.09 - 87.55%), while Inoviridae (58.16%) was the dominant family in PBI1. Cellulophaga phages (phi38:1 and phi10:1) and Flavobacterium phage 11b, infecting the possible host strains affiliated with the family Flavobacteriaceae of the phylum Bacteroidetes, were abundant in surface water dsDNA viromes. The long contig (PBI2_1_C) from the viral metagenomes were most similar to the genome architectures of Cellulophaga phage phi10:1 and Flavobacterium phage 11b from the Arctic Ocean. Comparative analysis showed that the surface viral community of Prydz Bay could be clearly separated from other marine and freshwater environments. The deep sea viral community was similar to the deep sea viral metagenomes at A Long-term Oligotrophic Habitat Assessment Station (ALOHA, at 22°45'N, 158°00'W). The multivariable analysis indicated that nutrients probably played an important role in shaping the local viral community structure. This study revealed the preliminary characteristics of the viral community in Prydz Bay, from both the surface and the deep sea. It provided evidence of the relationships between the virome and the environment in Prydz Bay and provided the first data from the deep sea viral community of the Southern Ocean.